MARKETING AND ADVERTISING STRATEGIES FOR THE LAUNCH OF AN ECO-FRIENDLY PAINT MADE FROM CRYSTAL PET: THE BIOPINT CASE - Nava, Itzayana Ortega; Rodríguez, Guadalupe Ortiz; Domínguez, Jasiel Cid; Roldán Y Tovar, Edgardo; Hernández, Jaime Rosas; Dionisio, Roberto Cesar Nepomuceno (Seven Editora, 2025)
The present article analyzes the influence of an ecological advertising campaign on the acceptance of the sustainable paint BioPint, produced using crystal PET waste and recycled Styrofoam in the communities of Ixcaquixtla and Tepexi de Rodríguez, Puebla. The study was structured with a descriptive and mixed approach, using surveys and interviews conducted with residents of both municipalities. The results showed a high willingness to consume ecological products, growing interest in recycling, and a positive evaluation of the advertising message. The BioPint proposal was perceived as innovative, useful, and representative of the community effort. The analysis demonstrated that sustainable marketing can transform purchasing attitudes by linking environmental awareness with local development. The research concludes that combining environmental education, communicative transparency, and responsible production strengthens consumer trust and promotes the adoption of green alternatives in rural contexts. DOI: https://doi.org/10.56238/sevened2025.036-072